17β-Hydroxysteroid dehydrogenase 3 deficiency: Three case reports and a systematic review. Issue 174 (November 2017) - Yang, Zuwei; Ye, Lei; Wang, Wei; Zhao, Yu; Wang, Wencui; Jia, Huiying; Dong, Zhiya; Chen, Yuhong; Wang, Weiqing; Ning, Guang; Sun, Shouyue
Highlights: First report on 17β-hydroxysteroid dehydrogenase 3 deficiency cases in East Asia with two novel mutations. Systematic review describing region-specific mutations based on different continents. Evidence for a decreasing tendency of germ cells and an increasing tendency of Leydig cells in testes with age in 17β-HSD3 deficiency patients. Abstract: 17β-Hydroxysteroid dehydrogenase 3 deficiency is a rare autosomal recessive cause of 46, XY disorders of sex development resulting from HSD17B3 gene mutations, however, no case has been reported in East Asia. The aim of this study was to report three Chinese 46, XY females with 17β-HSD3 deficiency in a single center and perform a systematic review of the literature. Clinical examination, endocrine evaluation and HSD17B3 gene sequencing were performed in the three Chinese phenotypically females (two sisters and one unrelated patient). Relevant articles were searched by using the term "HSD17B3" OR "17beta-HSD3 gene" with restrictions on language (English) and species (human) in Pubmed and Embase. All the three phenotypically female subjects showed 46, XY karyotype, inguinal masses, decreased testosterone and increased androstenedione. Two novel homozygous mutations (W284X and c.124_127delTCTT) in HSD17B3 gene were identified. A systematic review found a total of 121 pedigrees/158 patients, with 78.5% (124/158) of patients assigned as females, 15.2% (24/158) from females to males, and 5.1% (8/158) raised as males. The most common mutation was c.277 + 4C > T (allele frequency: 25/72) for patients from Europe, and R80Q (allele frequency: 21/54) for patients from West Asia. The testicular histology showed normal infantile testicular tissue in 100% (9/9) infantile patients, normal quantity germ cells in 44.4% (8/18) prepubertal patients and 19.0% (4/21) pubertal and adult patients. We reported the first East Asian 17β-hydroxysteroid dehydrogenase 3 deficiency cases. Additional literature reviews found founder effects among patients with different ethnic background and early orchiopexy may benefit fertility in patients assigned as males. These findings may significantly expand the clinical, ethnic and genetic spectrum of 17β-hydroxysteroid dehydrogenase 3 deficiency.